Analisis Rasio Keuangan untuk Mengevaluasi Kinerja Keuangan Perusahaan :Studi Kasus Pada PT. Indofood Sukses Makmus Tbk (INDF) Periode 2019 - 2023 - Silviezy Romyulaesi; Labib Zidan; Koirunisah; M. Masrukhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to evaluate and analyze the financial performance of PT Indofood Sukses Makmur Tbk (INDF) using financial ratios such as solvency, liquidity, profitability, and activity. This research uses quantitative methodology with an emphasis on numerical data. The data source used for analysis is the financial statements of PT Indofood Sukses Makmur Tbk (INDF) from 2019 to 2023. The results of the analysis conducted provide an overview of the financial condition of PT Indofood Sukses Makmur Tbk (INDF). The current ratio shows generally good performance, while the cash ratio and quick ratio are also in the “good” category. Because PT Indofood Sukses Makmur Tbk (INDF) is able to fulfill its obligations well in the long term, it can be concluded that the company can perform very well. This research is useful for investors, managers and other stakeholders involved in decision making based on accurate and reliable data from the financial industry.